Perioperative Durvalumab with Neoadjuvant Chemotherapy in Operable Bladder Cancer - Powles, Thomas; Catto, James W F; Galsky, Matthew D; Al-Ahmadie, Hikmat; Meeks, Joshua J; Nishiyama, Hiroyuki; Vu, Toan Quang; Antonuzzo, Lorenzo; Wiechno, Pawel; Atduev, Vagif; Kann, Ariel G; Kim, Tae-Hwan; et al. (The New England journal of medicine, 2024)
BACKGROUND: Neoadjuvant chemotherapy followed by radical cystectomy is the standard treatment for cisplatin-eligible patients with muscle-invasive bladder cancer. Adding perioperative immunotherapy may improve outcomes. METHODS: In this phase 3, open-label, randomized trial, we assigned, in a 1:1 ratio, cisplatin-eligible patients with muscle-invasive bladder cancer to receive neoadjuvant durvalumab plus gemcitabine-cisplatin every 3 weeks for four cycles, followed by radical cystectomy and adjuvant durvalumab every 4 weeks for eight cycles (durvalumab group), or to receive neoadjuvant gemcitabine-cisplatin followed by radical cystectomy alone (comparison group). Event-free survival was one of two primary end points. Overall survival was the key secondary end point. RESULTS: In total, 533 patients were assigned to the durvalumab group and 530 to the comparison group. The estimated event-free survival at 24 months was 67.8% (95% confidence interval [CI], 63.6 to 71.7) in the durvalumab group and 59.8% (95% CI, 55.4 to 64.0) in the comparison group (hazard ratio for progression, recurrence, not undergoing radical cystectomy, or death from any cause, 0.68; 95% CI, 0.56 to 0.82; P<0.001 by stratified log-rank test). The estimated overall survival at 24 months was 82.2% (95% CI, 78.7 to 85.2) in the durvalumab group and 75.2% (95% CI, 71.3 to 78.8) in the comparison group (hazard ratio for death, 0.75; 95% CI, 0.59 to 0.93; P = 0.01 by stratified log-rank test). Treatment-related adverse events of grade 3 or 4 in severity occurred in 40.6% of the patients in the durvalumab group and in 40.9% of those in the comparison group; treatment-related adverse events leading to death occurred in 0.6% in each group. Radical cystectomy was performed in 88.0% of the patients in the durvalumab group and in 83.2% of those in the comparison group. CONCLUSIONS: Perioperative durvalumab plus neoadjuvant chemotherapy led to significant improvements in event-free survival and overall survival as compared with neoadjuvant chemotherapy alone. (Funded by AstraZeneca; NIAGARA ClinicalTrials.gov number, NCT03732677; EudraCT number, 2018-001811-59.).
Keywords: senioři; Neoadjuvant Therapy; analýza přežití; senioři nad 80 let; Gemcitabine; nádory močového měchýře; Survival Analysis; doba přežití bez progrese choroby; Cisplatin; monoklonální protilátky; Middle Aged; Deoxycytidine; cisplatina; mužské pohlaví; Kaplan-Meier Estimate; Cystectomy; Kaplanův-Meierův odhad; Antibodies, Monoclonal; Adult; Aged, 80 and over; ženské pohlaví; Humans; deoxycytidin; Progression-Free Survival; neoadjuvantní terapie; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; gemcitabin; Urinary Bladder Neoplasms; protokoly protinádorové kombinované chemoterapie; adjuvantní chemoterapie; dospělí; protinádorové látky imunologicky aktivní; Female; Aged; Chemotherapy, Adjuvant; Antineoplastic Agents, Immunological; lidé; Male; cystektomie